Female pattern hair loss: A comprehensive review. Issue 6 (31st August 2020) - Bertoli, Mia J.; Sadoughifar, Roxanna; Schwartz, Robert A.; Lotti, Torello M.; Janniger, Camila K.
Abstract: Female pattern hair loss is a common form of hair loss in women that increases in incidence with age. The etiology is unknown with numerous factors identified that influence its onset. Female pattern hair loss may be viewed as a marker for an increased risk of cardiovascular and metabolic disease. New treatments include microneedling, low‐level laser therapy, and autologous fat transfer. This article focuses on the pathophysiology, diagnosis, systemic associations, and current treatments for female pattern hair loss, which is the most common cause of alopecia in women.